Sapiopsychosocial triage in obesity care - Sanjay Kalra; Madhur Verma; Atul Dhingra; Nitin Kapoor (Journal of the Pakistan Medical Association)
With the increasing prevalence of obesity, a triage systemis needed to prioritize access to obesity care services, aswell as support efficient choice of education andcounselling strategies. The sapiopsychosocial triage(SPST) system, based upon cognitive, psychological andsocial assessment of the person living with obesity, helpsdetermine the style and strategy of obesity management.It can be used as a complement to the Edmonton ObesityStaging System. The SPST ensures person –centreddelivery of chronic weight management, keeping thebiopsychosocial triad of health in mind. It facilitatesunderstanding of the myriad determinant causes andcontributors, and dynamic confounders of weight gain.Thus, it serves as a learning and teaching tool for all healthcare professionals.